Perfil de compostos voláteis de condensados obtidos a partir da fumaça gerada na torração do café - Santos, Gabriella (2013)
The pyrolytic process that occurs during roasting, generates Maillard and caramelization reactions, and forms a wide range of volatile compounds, being studied by many researchers, who have identified more than a thousand compounds. In the process of condensing the vapors are cooled below the dew point and then pass into liquid state. This work was performed at Polo Excellence Coffee/DAG, in the Central Laboratory of Analyses/DCA and Laboratory of Chromatographic Analysis/DQI/UFLA. The objective was to condense the smoke generated in the roasting coffee, from the elaboration of three condensers and drawing up the profile of volatile condensate compounds obtained at different degrees of roasting. The experiment was conducted in a complete factorial design 3x3 with the following factors and levels: condenser and roasting, being condensing bed, balloon of condensing and soxhlet extractor and light, medium and dark, respectively. The coffees were selected in 16 sieves. Samples of 2 kg were roasted in roaster Pinhalense TC-02 and classified according to the degree of roasting by the method Agtron-SCAA. The condensers were connected to roaster individually during the roasting process, getting the condensate. Analyses were made in the volatiles composition by GC/MS through SPME - Headspace methodology in the condensates and in the precursor’s coffees thereof. The results of the volatile composition were subjected to descriptive analysis. The color of condensates was analyzed, characterizing them regarding the parameters L* (sample brightness -0-black; 100-white), a* (intensity of the green to red) and C* (weak or strong color) and were evaluated by variance analysis (ANOVA) and Tukey test with 5% level of significance. It was possible to condense the smoke generated during the coffee roasting, through the three condensers developed. According to the composition of volatiles, the condensing bed is more efficient, because obtained condensates with volatile compounds of impact character of the coffee. The best condensate were obtained from the dark roast, where characterized by color strong, with a larger number of impact character compounds and a greater amount of compounds detected.